Adoptive CD8+ T cell therapy against cancer:Challenges and opportunities. (10th October 2019) - Jiang, Xiaotao; Xu, Jiang; Liu, Mingfeng; Xing, Hui; Wang, Zhiming; Huang, Lei; Mellor, Andrew L.; Wang, Wei; Wu, Sha
Abstract: Cancer immunotherapy is a new and promising option for cancer treatment. Unlike traditional chemo- and radiotherapy, immunotherapy actives host immune system to attack malignancies, and this potentially offers long-term protection from recurrence with less toxicity in comparison to conventional chemo- and radiation therapy. In adoptive CD8 + T cell therapy (ACT), large numbers of tumor-specific T cells are sourced from patients and expanded in vitro and infused back to patients. T cells can be expanded from naturally-induced tumor-specific CD8 + T cells isolated from tumor infiltrating lymphocytes (TIL) or genetically-modified autologous circulating CD8 + T cells. The engineered T cells expressed tumor-specific antigen receptors including chimeric antigen receptors (CARs) and T cell receptors (TCRs), prepared from cultured B and T cell clones, respectively. The most successful ACT, anti-CD19 chimeric antigen receptor T (CAR-T) cell therapy directed against B cell lymphoma, is already approved for use based on evidence of efficacy. Efficacy of solid tumors is not yet forthcoming. This review summarizes current technology developments using ACT in clinical trials. In this review, differences between various ACT approaches are discussed. Furthermore, resistance factors in the tumor microenvironment are also considered, as are immune related adverse effects, critical clinic monitoring parameters and potential mitigation approaches. Highlights: Adoptive CD8 + T cell therapy against cancer starts to achieve encouraging results. CAR-T and TCR-T of gene-engineered T cells strengthens the CD8+T cell-based immunotherapy. Tumor antigen mutation, tumor microenvironment, short persistence of T cells and toxicity obstruct immunotherapy.